Flexural capacity of CFRP-strengthened reinforced concrete beam with circular web openings in flexure zone - Abdul Hamid, Noor Azlina; Tengku Daeng Johar, Tengku Daeng Dinie Afiq; Salleh, Norhafizah; Ali, Noorwirdawati; Abdullah, Siti Radziah; Adnan, Suraya Hani; Jamellodin, Zalipah; Md. Noor, Nurazuwa; Othman, Nor Hazurina (Penerbit UTHM, 2020)
In modern building structure, most of reinforced concrete member such as column, beam and slab commonly consists of opening for utility services, such as water supply, air conditioning system and sewerage. However, the presence of openings may affect the flexural performance of concrete structures due to the changes of its cross sectional dimension. This study aims to investigate the flexural capacity of reinforced concrete beams with circular opening and strengthened using bi-directional Carbon Fiber Reinforced Polymer (CFRP) sheet. The beam specimens with size of 200 mm (width) x 250 mm (height) x 1700 mm (length) were casted with normal grade concrete of 52 N/mm2 and tested until failure. The beam consists of control beam which was casted without opening, reinforced concrete beams with circular opening and strengthened reinforced concrete beams with opening. The circular opening with diameter of 150 mm was provided at the middle of beam span. From the beam test results, beam with opening was obtained similar ultimate load capacity as control beam. However, beam with opening experienced higher deformation as compared to control beam. By strengthen the opening of beam with bi-directional CFRP wraps, the ultimate load capacity of the beam increases and deformation of the beam reduces.